Detection of ECG artefacts in horses: comparison between textile and standard electrodes - Lanatà, A.; Guidi, A.; Scilingo, E. P.; Sighieri, C.; Baragli, P. (DCA Report; Nr. 044, 2014)
In this work, we compared standard (FS50LG, EF Medica™) and textile electrode (Smartex™) performance for acquiring ECG signal from horses. The textile electrodes were completely integrated in a textile support and were realized by combining conductive yarn (based on stainless steel fibres) and elastane. A multi-layered structure is used to increase the quality of the skin-electrode contact. Two identical devices were used for the simultaneous ECG acquisition with standard (Std-E) and textile (Tex-E) electrodes. Both Tex-E and Std-E were placed at the same positions on the chest (without shaving) through a chest belt. The signals from the Tex-E and Std-E were continuously acquired by a dedicated electronics (3 x 2 x 0.5 cm) that wirelessly transmits the data to a remote station through 802.11b communication protocol. Performances of both electrodes were evaluated by comparing the percentages of ECG artefacts in the two simultaneous acquisitions. Seven horses were recruited in a two-phase experimental session. In the first phase, horses were free to move in the stall for one hour (T60) while ECG was acquired. Afterwards, signal acquisition continued with a 15 minute walk in-hands along a standardised pathway (T15). The ECG signals were pre-filtered in order to remove the baseline and the high frequency noise; afterwards they were segmented in windows in which at least one complete QRS complex was present. A signal processing algorithm to estimate the motion-induced artefacts was developed based on Stationary Wavelet Transform using a multi-resolution threshold method. The percentage of artefacts was then analysed with paired t-test (P<0.05). The Bland-Altman plot revealed correlation between Std-E and Tex-E electrodes. Furthermore, a statistically significant lower percentage of ECG artefacts was detected with Tex-E than Std-E in both T60 (8.1±1.7 vs. 12.3±3.0, n=7, t6=-4.58, P=0.0038) and T15 (29.6±6.9 vs. 56.7±20.1, n=7, t6=-4.64, P=0.0035). In addition to well-known advantages of comfort and simplicity in using, textile electrodes showed better technical performances than standard electrodes. Although preliminary, these good results indicate that smart textiles can be profitably employed to collect short term ECG in horses, both during rest and light physical activity. LP: After proper "gold standard" validation, textile platforms could be easily adopted in horses to collect parameters related to Autonomic Nervous System activity, such as heart rate variability, respiratory rate, peripheral measures of cardiovascular and respiratory functioning, electro-dermal response, skin secretion of stress-related hormones, etc.